Fuel Physical Characteristics of Biodiesel Blend Fuels with Alcohol as Additives - Mohd Hafizil, Mat Yasin; R., Mamat; Ahmad Fitri, Yusop; Rafidah, Rahim; Amir, Aziz; Liyana, Amer Shah (Elsevier Ltd, 2013)
Biodiesel and its alcohol blend fuels are considered as alternatives to current fossilized fuels. Their fuel physical characteristics are among the most important parameter to determine the quality of each fuel. Strict procedures are used in observation and measurement to obtain the flash point, viscosity, density, acid value and Cetane number in order to define the actual properties of biodiesel and its alcohol blend fuels. These obtained properties are very beneficial to be used in any arithmetical simulation for further findings. These properties provide good explanations on how the engine operates with those fuels in terms of performance, combustion and emission characteristics. Biodiesel and its alcohol blend fuels analysis were conducted in UMP Chemical laboratory using different analytical apparatus including viscosity bath, acid value & acidity tester, density meter and bomb calorimeter. Properties comparison were been made between mineral diesel, B100, B20 and B20 alcohol blend fuels. The results show that the presence of alcohol helps to reduce the viscosity and density of biodiesel concentration when blending with mineral diesel. On other hand, a significant increase in Cetane number as a result of an increase in alcohol concentration in the biodiesel blend fuels. However, the properties of biodiesel and its alcohol blend fuels still meet the requirement of EN14214.